2017
DOI: 10.7860/jcdr/2017/21567.9524
|View full text |Cite
|
Sign up to set email alerts
|

Chaput Tubercle Fracture in an Adult- A Rare Case Report

Abstract: A 33-year-old male presented to the causality of the hospital after encountering a road accident about an hour ago. The patient experienced a head on collision with another bike while driving his two wheeler. The patient complained of pain, contusion and swelling over the anterior aspect of left ankle. On examination, tender swelling with pain and restricted movement of ankle was noted. No associated history of vomiting, unconsciousness or any related injuries was found except the superficial abrasion over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 5 publications
1
9
0
3
Order By: Relevance
“…CT scan) to evaluate all fracture planes, but also to detect other fractures, articular fragments and articular compatibility. 1,6,8,20,21 It should be noted that Liporace et al did not found inter-and intra-observer differences in primary treatment plans between radiographs and radiographs plus CT. 24 Recently, Ito et al reported the first malunion case in a CTF, following conservative treatment, where a corrective osteotomy at the original fracture side was performed to due to persistent pain five months post-injury. 4 Nevertheless, it was not an isolated CTF-a concomitant medial fracture was also detected by the time of sprain.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…CT scan) to evaluate all fracture planes, but also to detect other fractures, articular fragments and articular compatibility. 1,6,8,20,21 It should be noted that Liporace et al did not found inter-and intra-observer differences in primary treatment plans between radiographs and radiographs plus CT. 24 Recently, Ito et al reported the first malunion case in a CTF, following conservative treatment, where a corrective osteotomy at the original fracture side was performed to due to persistent pain five months post-injury. 4 Nevertheless, it was not an isolated CTF-a concomitant medial fracture was also detected by the time of sprain.…”
Section: Discussionmentioning
confidence: 92%
“…6,[9][10][11][12][13] The vulnerable growth plate may not be fused until 14 years in girls and 18 years of age in boys. [6][7][8]11,14,15 The adult Tillaux fracture, also recognized as CTF, has a relative incidence of 12% in transmalleolar fractures but the frequency as isolated bony avulsion remains unknow. [16][17] It is classified as AO/OTA43B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feng et al in 2018 8 However, as in our case, previous studies reporting open reduction, did not report evidence of complications or infection. 2,9,10,11,6,5,4,12,3,13 Regarding X-ray assessment of articular alignment in closed reduction versus intraarticular direct surface assessment in open reduction, no evidences of poor functional mid-term outcomes have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…1 Esse tipo de lesão é raramente observado em adultos com maturidade esquelética porque o ligamento tibiofibular anterior geralmente se rompe primeiro. [2][3][4][5] As fraturas intra-articulares requerem redução e estabilização anatômicas para evitar complicações como instabilidade do tornozelo, dor no tornozelo e osteoartrite pós-traumática. 4,6 A artroscopia tem várias vantagens em relação às abordagens abertas, permitindo um tratamento menos agressivo das lesões associadas, melhora da redução intra-articular e com menos complicações.…”
Section: Introductionunclassified